2012
DOI: 10.3892/ol.2012.595
|View full text |Cite
|
Sign up to set email alerts
|

Adrenalectomy may increase survival of patients with adrenal metastases

Abstract: Abstract. The much improved diagnostic accuracy of computed tomography (CT) and positron emission tomography (PET) has enabled urologists and medical oncologists to identify and treat more patients with metastases to the adrenal glands. The aim of this retrospective study was to analyze the clinical aspects of adrenal metastases in a series of patients and to evaluate the effect of adrenalectomy, by laparoscopic or open resection of adrenal metastases, on the survival of these patients. A total of 47 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 16 publications
2
40
0
Order By: Relevance
“…However, in cases of isolated adrenal metastases survival can be improved after adrenalectomy [3,[11][12][13]. In our 19 patients with isolated adrenal metastases, the mean estimate survival was 25.0 months, which according to the results of other authors [6,[15][16][17].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…However, in cases of isolated adrenal metastases survival can be improved after adrenalectomy [3,[11][12][13]. In our 19 patients with isolated adrenal metastases, the mean estimate survival was 25.0 months, which according to the results of other authors [6,[15][16][17].…”
Section: Discussionsupporting
confidence: 61%
“…Long-term survival rates have been reported in patients after adrenalectomy due to metastatic disease, provided there was an isolated metastasis [3,[11][12][13]. In terms of surgical approach, numerous authors have reported safety and similar oncological results of laparoscopic adrenalectomy for metastases compared to open surgery [11,12,[14][15][16].…”
Section: Introductionmentioning
confidence: 92%
“…There is some evidence for survival advantage for surgical intervention for oligometastatic disease of the adrenals [80][81][82][83][84]. Other treatment approaches to oligometastatic disease include CT-guided ablation [85], radiotherapy, and stereotactic radiation treatments [86,87].…”
Section: Adrenal Metastasesmentioning
confidence: 98%
“…11,12 Surgery can be performed with an open resection or through laparoscopic approach. Laparoscopic adrenalectomy has been shown to improve patients' morbidity and to reduce hospitalization with a comparative oncological outcome compared to the open resection technique.…”
Section: Introductionmentioning
confidence: 99%